Comprehensive Atlas of the Myelin Basic Protein Interaction Landscape - Evgeniya V. Smirnova (MDPI AG, 2021)
Intrinsically disordered myelin basic protein (MBP) is one of the key autoantigens in autoimmune neurodegeneration and multiple sclerosis particularly. MBP is highly positively charged and lacks distinct structure in solution and therefore its intracellular partners are still mostly enigmatic. Here we used combination of formaldehyde-induced cross-linking followed by immunoprecipitation and liquid chromatography-tandem mass spectrometry (LC-MS/MS) to elucidate the interaction network of MBP in mammalian cells and provide the list of potential MBP interacting proteins. Our data suggest that the largest group of MBP-interacting proteins belongs to cellular proteins involved in the protein translation machinery, as well as in the spatial and temporal regulation of translation. MBP interacts with core ribosomal proteins, RNA helicase Ddx28 and RNA-binding proteins STAU1, TDP-43, ADAR-1 and hnRNP A0, which are involved in various stages of RNA biogenesis and processing, including specific maintaining MBP-coding mRNA. Among MBP partners we identified CTNND1, which has previously been shown to be necessary for myelinating Schwann cells for cell-cell interactions and the formation of a normal myelin sheath. MBP binds proteins MAGEB2/D2 associated with neurotrophin receptor p75NTR, involved in pathways that promote neuronal survival and neuronal death. Finally, we observed that MBP interacts with RNF40–a component of heterotetrameric Rnf40/Rnf20 E3 ligase complex, recruited by Egr2, which is the central transcriptional regulator of peripheral myelination. Concluding, our data suggest that MBP may be more actively involved in myelination not only as a main building block but also as a self-regulating element.